PLAYING AGE-APPROPRIATE ACTIVITY GAMES FOR PRE-SCHOOL CHILDREN (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This article describes the sequence of appropriate development of emotions and physical qualities and improvement of movement skills in preschool children through active games.